THE IMPACT OF EXCESSIVE STUDY HOURS IN THE AL AZHAR MEDAN SENIOR HIGH SCHOOL ENVIRONMENT - Syekhariandi Siddik; Gavin Fattah; Audrey Harmoni; Mayfirdha Aulia; Adzra Alya (CV. RADJA PUBLIKA, 2024)
This study aims to explore the impact of excessive study hours on students' mental and physical health. In the context of modern education, many students experience pressure to achieve high academic results, which often results in unbalanced study hours. Through qualitative and quantitative methods, this study collected data from 20 students in various classes of SMA AL-Azhar Medan. The results showed that students who studied more than 10 hours per day tended to experience increased levels of stress, anxiety, and sleep problems. In addition, negative impacts were also seen on physical health, with increased complaints such as headaches, drowsiness and fatigue. These findings highlight the need for a more balanced approach to managing study hours, as well as the importance of interventions from schools and parents to support student well-being. Recommendations for healthier educational policies and learning practices are presented as an effort to create a sustainable learning environment.